Meningeal sporotrichosis in an immunocompetent host: A case report - Victor Teatini Ribeiro; Rachel Basques Caligiorne; Aldrin Pedroza Martins; Antônio Pereira Gomes Neto; Paulo Pereira Christo (Medical Mycology Case Reports, 2024)
A 78-year-old woman presented to hospital with altered mental status. Hyponatremia was diagnosed and treated. She maintained mental confusion despite normal sodium. No headache, fever or focal signs were present. CSF analysis showed chronic meningitis; MRI demonstrated basilar enhancement. She was empirically treated for tuberculosis, with no improvement. PCR for Sporothrix in the CSF was positive. After treatment with Amphotericin followed by oral itraconazole, she completely recovered her cognitive abilities. Follow-up CSF was normal. This report illustrates the need to consider sporotrichosis in the differential diagnosis of chronic meningitis in immunocompetent, and the importance of PCR as a diagnostic tool.